Knowledge, Attitudes, and Perceptions of Mental Disorders Among Young Adults: Addressing Stigma and the Need for Mental Health Care - Barmashakha, Siwani; Dhaubhadel, Sarita (International Journal of Atharva, 2024)
This study explores the knowledge, attitudes, and perceptions of young adults towards mental disorders and mental health care needs. Using a quantitative research design, data was collected from 170 participants via a structured questionnaire administered online. Descriptive statistics were employed to analyze the data, revealing key insights into demographic characteristics and respondents' views on mental health. The findings indicate a strong consensus on the importance of mental health as a vital component of overall well-being, with moderate agreement on the causes of mental disorders, such as brain diseases, genetic inheritance, and drug abuse. However, misconceptions persist, particularly regarding supernatural causes and the stigma associated with mental illness. While young adults generally hold positive attitudes towards individuals with mental disorders, some stigmatizing beliefs still exist. The study also highlights a widespread recognition of the need for mental health care, with an overwhelming majority of respondents advocating for professional help and open discussions about mental health concerns. These findings underscore the necessity of addressing mental health stigma and promoting awareness and education among young adults to foster a more supportive and understanding environment for those affected by mental disorders.